Análise da presença do glicerol no comportamento fluidodinâmico de leitos fluidizados e vibrofluidizado - Daleffe, Roger Valeri (2002)
Vibrofluidized beds with inert particles are often used for drying pastes in a laboratory scale. Aiming to contribute to the study of paste drying in such beds, the main purpose of this work is to analyze fluid dynamic behavior of fluidized and vibrofluidized beds as a function of parameters such as the inert particle diameter, the bed temperature, the vibrational parameter and the liquid saturation rate in the bed (defined as the quotient volume of liquid/volume of particles). Curves of pressure drop fluctuations as a function of time were obtained for the tri-phase system and the effect of those parameters on the mixture minimum velocity (as proposed by Gupta and Mujumdar, 1980a) were also analyzed. As liquid phase was employed glycerol, which have been fed into the bed in a batch mode. Glycerol was chosen because it suffers practically no evaporation at the experimental conditions. As inert particles were employed glass spheres in group D of Geldart´s classification. The vibrofluidized bed was of galvanized steel, with square-cross section of 0.20x1.10 m and height of 0.20 m. Pressure drop data and superficial air velocity data were collected by pressure transducers connected to an acquisition data system. The data were collected for vibrational ranges from 0.00 to 1.50; mean particle diameters of 1.095x10-3, 1.545x10-3 e 1,850x10-3 m; bed temperatures of 40, 50 and 60 oC and saturation rates from 0.0000 to 0.0040. The results indicate that the bed temperature does not affect significantly the pressure drop curves behavior. The vibrational parameter also shows little influence on pressure drop versus air velocity curves, excepting in the transition between fluidized and vibrofluidized beds. On the other hand, the pressure drop curves behavior is strongly affected by the increasing of the liquid saturation rate and by variation of particle diameter. Analysis of standard deviation of pressure drop fluctuations shows that for conditions which are typical of a fixed bed, the standard deviations are very small and almost independent on every parameter investigated. At fluidized bed conditions, these standard deviations are significant, particularly at the greatest air velocities. It was observed that they increase a lot in the presence of vibration, even at fixed bed conditions. Besides providing additional information on the bed fluid dynamic behavior, the curves of standard deviation of pressure drop fluctuations are also useful to identify the beginning of particle displacement into the bed due to vibration. It was observed that the methodology applied to identify the minimum fluidization velocity did not provide good results, but it worked well to identify the mixture minimum velocity as defined by Gupta and Mujundar (1980a). For the conditions investigated, the mixture minimum velocity is strongly affected by the liquid saturation rate and by the particle diameter, while both the bed temperature and the vibrational parameter show little influence on it.